Learning in the Field of Geographic Information Systems: Experiences, Suggestions and Challenges - Urh, Marko; Jereb, Eva (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The article discusses leaning in the field of geographic information systems at the Faculty of Organizational Sciences of the University of Maribor, namely in the Crisis Management study program of higher professional studies. Geographic information systems are one of the key elements of every serious organization that deals with crisis events. The use of geographic information systems requires a lot of interdisciplinary knowledge in the fields of informatics, databases, programming, statistics, cartography and, of course, the field in which it is used. Therefore, education in the field of the aforementioned systems is also demanding and long-term. The basic building blocks of geographic information systems are hardware and software, data, methodology and people. With the thoughtful use of geographic information systems, we can more easily and better understand events before, during and after crisis situations and thus also their mutual connections, patterns and characteristics. The article describes the characteristics and suggestions that we have acquired in educational practice. The recommendations relate to work with students, and show proven approaches and methods for conducting lectures and exercises, as well as recommendations for installing, managing and maintaining the system itself, and more. Some suggestions are given to eliminate students' discomfort, as some of them are encountering such complex information systems for the first time.